Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/jmv.23678
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and quantitation of adenovirus DNA from human tonsil and adenoid tissues

Abstract: In this study, real-time PCR was used to quantify adenovirus DNA in cell suspensions prepared from 106 right and left tonsils and 10 adenoids obtained from 57 patients who underwent routine tonsillectomies and/or adenoidectomies. Eighty-four (72.4%) tonsils and adenoids samples were positive for HAdV by real-time PCR. The viral load ranged from 2.8 × 10(2) to 2.6 × 10(6) copies/10(7) cells and varied up to sixfold between the right and left tonsils. In some cases, only one tonsil was positive and the viral loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 45 publications
2
22
1
Order By: Relevance
“…This value is higher than reported in our previous study (19.3 %) (Rynans et al 2012), but similar to described by other authors (32.2-44.8 %) (BilLula et al 2010;Ganzenmueller et al 2011). Single positive results could be considered less important from clinical point of view due to possible persistent (latent) HAdV infection has been shown to occur even in healthy individuals (Alkhalaf et al 2013). The majority of alloHSCT recipients in our study with detectable DNAemia within the first 10 weeks after transplantation had only FUO.…”
Section: Discussioncontrasting
confidence: 55%
“…This value is higher than reported in our previous study (19.3 %) (Rynans et al 2012), but similar to described by other authors (32.2-44.8 %) (BilLula et al 2010;Ganzenmueller et al 2011). Single positive results could be considered less important from clinical point of view due to possible persistent (latent) HAdV infection has been shown to occur even in healthy individuals (Alkhalaf et al 2013). The majority of alloHSCT recipients in our study with detectable DNAemia within the first 10 weeks after transplantation had only FUO.…”
Section: Discussioncontrasting
confidence: 55%
“…We and other investigators have identified adenoviral DNA in mononuclear cells from adenoids and tonsils of children as young as two years [13,14,29]. By four years of age virtually every child is carrying one or more adenoviral genotypes in their mucosal tissues [13].…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of adenovirus-positive lymphocytes in the peripheral blood at this time likely differs from that in cord blood at birth. Although adenoviral DNA is found in pediatric adenoid and tonsil lymphocytes [13,14,29,38], it is rarely detected in peripheral blood lymphocytes [39,40]. Interestingly, immature T and B cells are more abundant in pediatric adenoids and tonsils than in other secondary lymphoid tissues [4143].…”
Section: Discussionmentioning
confidence: 99%
“…Although Ad5 infected RM and humans develop potent neutralizing antibody responses and Ad5-specific T cells responses [10], [18][25], [32], the pattern of virus shedding suggests that this immunity does not prevent re-infection. Further anti-Ad5 immunity is often incapable of completely clearing Ad5 infections as the virus can persist in mucosal surfaces of humans [8] and RM [9] for months.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of Ad5 in North American and other populations has been assessed serologically; almost all subjects tested have Ad5-specific binding antibodies, of which 30–60% also have neutralizing antibody responses [5][7]. Adenoviruses infect a broad range of animals in a relatively species-specific manner and adenoviruses can be persistently shed in respiratory secretions and stool [8][11]. Adenoviruses isolated from macaque monkey species (rhesus, cynomologus) are in a different phylogenetic group from the human adenoviruses and do not segregate with human Ad5 or other Group C adenoviruses [11].…”
Section: Introductionmentioning
confidence: 99%